The The Influence of Love of Money, Lifestyle, Machiavellianism, and Ethical Knowledge on the Ethical Perceptions of Accounting Students in Indonesia - Juliofano, Reki (Amkop Management Accounting Review (AMAR), 2026)
This study aims to identify and examine the factors influencing the ethical perceptions of Generation Z accounting students in Indonesia, considering the roles of Love of Money, lifestyle, Machiavellian traits, and ethical knowledge. A quantitative approach was employed using a survey method, with questionnaires distributed to 276 respondents selected through purposive and convenience sampling techniques. The collected data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS software version 4.1.1.6 to assess both the measurement and structural models. The results indicate that Love of Money has a positive and significant effect on students' ethical perceptions, suggesting that monetary orientation can coexist with ethical considerations in decision-making. Lifestyle also demonstrates a positive and significant impact on ethical perceptions, showing that students' habits, consumption patterns, and social environments shape their ethical judgments. In contrast, Machiavellianism does not significantly affect ethical perceptions, indicating that manipulative tendencies are not dominant factors in the moral evaluations of Generation Z accounting students. Ethical knowledge emerges as the strongest factor shaping students' ethical perceptions among examined variables. These findings highlight the importance of strengthening ethics education in higher education to develop prospective accountants with integrity who are capable of making responsible professional decisions